The Effect of STEM-Based Worksheet on Students’ Science Literacy - Sulistiyowati, Sulistiyowati; Abdurrahman, Abdurrahman; Jalmo, Tri (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2018)
This study aims to improve the students’ science literacy through the application of STEM-Based Worksheet (Science, Technology, Engineering, and Mathematics) on sound waves learning the material. The research used mixed-method with exploratory sequential design in the Nonequivalent Control Group Design. Samples were taken using purposive sampling technique. This study involved 25 eighth grade students of class F as the experimental class and 25 eighth grade students of class A as the control class in SMP Negeri 2 Pugung. The data collecting techniques were observation method, questionnaire, and test. The data were analyzed using independent sample t-test to see the effectiveness of the learning in both groups. The questionnaire results were analyzed descriptively. The results showed that the application of STEM-based worksheet could effectively increase the science literacy with N-gain of 0.43 (medium category). The highest increase was in the indicator of “explains the science phenomenon" and the lowest was on the "drawing conclusions" indicator. The results of the students’ questionnaire responses after using the developed worksheet was 92,73 (very high category). This means that the developed students’ worksheets effective in increasing science literacy.